방문간호사업에 대한 대상자의 인식에 관한 연구 - 민영선(Young Sun Min); 정연강(Yeoun Kang Chung); 한승의(Seung Eui Han) (지역사회간호학회지, 2000)
In this, analyzing the type of subjectivity in which people would have about home visit nursing services originating from public health care centers. I tried to research more effective ways to improve home visit nursing care services. and later. for the development of home visit nursing care. to supply basic data. The method for this study was the Q-method. created by William Stephenson. and was adequate for the study of subjectivity. For this study. through the deep interview. literature inquiry, and the discussion course. 206 Q-statement sentences were abstracted. and based on them, after Q-sample-selection. I then collected the Q-categorized-result from 32 subjects from Mar. 10. 2000 to Mar. 25. 2000. Through the statistic a analysis of PC-Qunal program. the subjectivity species were categorized and analyzed. The study results show that there are 3 sorts of recognition types. and they are analyzed in the following; The first type: the positively receiving type shows that they feel thankful and a trusting feeling about home visit nursing. The second type: the negatively mistrusting type shows that they had doubtful attitudes about the specialty of home visit nursing: they wanted medicine or nutrition remedies rather than health education and concerning the their own health care, they prefered the hospitals or clinics. The third type: the conditional receiving type shows that even though they had a positive receiving attitude about home visit nursing wanting to consult with the home visit nurses about the difficult problem which could not easily be settled, hoping that the home visit nurses could visit them more often, in their actual lives. they strongly indicated their attitudes concerning money as more important than home visits. The subjects in these 3 types commonly had a good feeling about the kindness of the home visit nurses: the first and third types also had a positive recognition about home visit nursing; however. in aspects of the evaluation and receiving attitudes, they showed a big difference. When all the above results are integrated. in the case of the first type the home visit nursing service, which satisfied the demand for health care of the medically weak people. should be continuously supplied. Additionally in case of the second type (negatively mistrust). continuous education and support should be supplied with enough interest to lead their concerns about their own health care as well as lead medical spending in a productive and effective direction in order to change their impressions. Through this study. I learned that the recognition of the objectives of home visit nursing services can be categorized in to 3 types and could be analyzed. Thus I wish that this study helps to present basic data which contributes to the development of the home visit nursing field.